Intertextuality in Tragedy and Crime Fiction in Shakespeare’s Othello, Webster’s The Duchess of Malfi, Christie’s Curtain and Sleeping Murder - Dabbagh, Tara (Al-Adab Journal, 2019)
Christie maneuvers the storylines of Shakespeare’s Othello (c. 1604) and Webster's The Duchess of Malfi (1613/14) into crime fiction in, respectively, Curtain (1975) and Sleeping Murder (1976), establishing the actions of certain characters as patterns of behavior. Yet, despite the similarities in the four texts, and in accordance with the requirements of her genre, she does not allow the resulting structuralist intertextuality diminish the suspense in her stories. Unlike the tragedies which aim at emotional involvement, her two books